Design for patient safety: a systems-based risk identification framework. Issue 8 (3rd August 2018) - Simsekler, M. C. Emre; Ward, James R.; Clarkson, P. John
Abstract: Current risk identification practices applied to patient safety in healthcare are insufficient. The situation can be improved, however, by studying systems approaches broadly and successfully utilised in other safety-critical industries, such as aviation and chemical industries. To illustrate this, this paper first investigates current risk identification practices in the healthcare field, and then examines the potential of systems approaches. A systems-based approach, called the Risk Identification Framework (RID Framework), is then developed to enhance improvement in risk identification. Demonstrating the strengths of using multiple inputs and methods, the RID Framework helps to facilitate the proactive identification of new risks. In this study, the potential value of the RID Framework is discussed by examining its application and evaluation, as conducted in a real-world healthcare setting. Both the application and evaluation of the RID Framework indicate positive results, as well as the need for further research. Practitioner Summary: The findings in this study provide insights into how to make a better amalgamation of risk identification inputs to the safer design and more proactive risk management of healthcare delivery systems, which have been an increasing research interest amongst human factor professionals and ergonomists.